Handlebar injury in children: Are we ignoring the signs? - R. Fernández; P. Bragagnini; N. Álvarez; R. Delgado; J.P. Garcia; R. Escartín; J. Gracia (Elsevier, 2015)
The diagnosis of blunt intestinal injury in children is difficult and often delayed. We describe two cases of delayed diagnosis of intestinal injury following handlebar injury with abdominal wall tattooing. We review the literature to try and determine the usefulness of handlebar tattooing characteristics as a clinical sign for underlying small bowel injury in order to reduce delayed treatment. We propose a management algorithm for patients with handlebar tattooing.